Intervensi Edukatif terhadap Cyberbullying, Kekerasan Berbasis Gender Online, dan Kesadaran Hukum UU ITE di Kalangan Remaja SMK: Educational Intervention on Cyberbullying, Online Gender-Based Violence, and Legal Awareness of the ITE Law among Vocational High School Students - Ainani, Muhammad; Akhmad, Bachruddin Ali; Astuty, Sri; Sarwani, Sarwani; Hamdie, Nur Tazkia Amalia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program aims to enhance digital literacy among students of SMK Negeri 1 Banjarmasin, focusing on preventing cyberbullying and online gender-based violence (OGBV), and on improving legal awareness through Indonesia's Information and Electronic Transactions Law (UU ITE). The program was conducted through a series of activities, including pre-test, socialization, digital skills training, mentoring, and post-test evaluation. A total of 501 students participated, with the majority aged 15–16 years and predominantly female. The results revealed a significant increase in students' understanding of digital literacy concepts. Knowledge of OGBV increased from 65 percent in the pre-test to 89.0 percent in the post-test. Understanding of cyberbullying rose from 60 percent to 87.8 percent, while knowledge of UU ITE improved from 62 percent to 88.6 percent. Beyond theoretical knowledge, students also demonstrated practical skills in managing privacy settings, reporting harmful content, and producing positive digital content using social media platforms. This program confirms that an interactive, school-based, and contextual approach is effective in improving youth digital literacy, although challenges such as high gadget usage and weak parental supervision remain to be addressed. The success of this program is expected to serve as a model for school-based digital literacy initiatives that can be replicated in other educational communities.